Optimization of ejector based multi-evaporator refrigeration system - Teo, Jasmine Hui Hui. (2012)
Refrigerated shipping containers are widely used in transportation to provide customers with safe and high quality perishable goods. Driven primarily by the expansion of the chilled and quick-frozen foods market, refrigerated transport is a major economic player. As such, the growth for refrigerated shipping containers will continue to increase. Typically, evaporating temperatures of -30°C, -5°C and +7°C are required for freezing food, perishable food and space cooling respectively. An ejector based multi-evaporator refrigeration system (EMERS) which consists of a single refrigeration system with one compressor, two ejectors and three evaporators will be used for this project. The opening sizes of the EEVs, the compressor frequency and the condenser frequency will be adjusted to obtain the critical operating points of the system that will be needed for the optimization of the system. The experimental procedures and an analysis of the testing results will be included together with the suggestions for future improvements that can be made.